Application of Phenylephrine After Cardiac Surgery in Children with Low Cardiac Output Syndrome (Herald of the National Children's Medical Center, 2025)
One of the most severe complications in the early postoperative period in children after cardiac surgery is low cardiac output syndrome (LCOS). Despite the development of neonatal and pediatric cardioreanimation, there are still no standardized recommendations for the use of vasoactive agents in LCOS in children. Therefore, evaluating the effectiveness of phenylephrine as part of the comprehensive therapy for LCOS in younger children is of particular interest.
Keywords: phenylephrine; children; low cardiac output syndrome; hemodynamics; inotropic therapy